2021
DOI: 10.1093/plphys/kiab348
|View full text |Cite|
|
Sign up to set email alerts
|

A genetic approach reveals different modes of action of prefoldins

Abstract: The prefoldin complex (PFDc) was identified in humans as a co-chaperone of the cytosolic chaperonin T-COMPLEX PROTEIN RING COMPLEX (TRiC)/CHAPERONIN CONTAINING TCP-1 (CCT). PFDc is conserved in eukaryotes and is composed of subunits PFD1 to 6, and PFDc-TRiC/CCT folds actin and tubulins. PFDs also participate in a wide range of cellular processes, both in the cytoplasm and in the nucleus, and their malfunction causes developmental alterations and disease in animals and altered growth and environmental responses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 57 publications
(110 reference statements)
1
32
0
Order By: Relevance
“…Prefoldin is involved in actin and tubulin stability in eukaryotes (Martin‐Benito et al, 2002; Wang et al, 2015). In Arabidopsis , all PFDs contribute to microtubule dynamics and organization (Gu et al, 2008; Rodriguez‐Milla and Salinas, 2009; Perea‐Resa et al, 2017; Blanco‐Touriñán et al, 2021). Since AtURI can interact with PFD2 and PFD6, it is possible that the actin and/or tubulin networks are altered in the aturi‐1 mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prefoldin is involved in actin and tubulin stability in eukaryotes (Martin‐Benito et al, 2002; Wang et al, 2015). In Arabidopsis , all PFDs contribute to microtubule dynamics and organization (Gu et al, 2008; Rodriguez‐Milla and Salinas, 2009; Perea‐Resa et al, 2017; Blanco‐Touriñán et al, 2021). Since AtURI can interact with PFD2 and PFD6, it is possible that the actin and/or tubulin networks are altered in the aturi‐1 mutant.…”
Section: Resultsmentioning
confidence: 99%
“…In the nematode Caenorhabditis elegans and the fruit fly Drosophila melanogaster , PFD‐deficient cells show low tubulin levels and several cytoskeleton abnormalities (Lundin et al, 2008; Delgehyr et al, 2012). In Arabidopsis , all PFD members participate in microtubule dynamic organization and pfd mutants exhibit impaired cell elongation and division (Gu et al, 2008; Rodriguez‐Milla and Salinas, 2009; Perea‐Resa et al, 2017; Blanco‐Touriñán et al, 2021). Besides their concerted role in the PFD complex, individual subunits may affect abiotic stress responses or contribute to gene expression (Blanco‐Touriñán et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutant of Arabidopsis that harbored deletions of all six prefoldin subunits was viable, and loss of the prefoldin complex did not significantly alter plant development under normal growth conditions. The prefoldin complex knockout mutant performed better than the wild type under osmotic stress conditions ( Blanco-Touriñán et al, 2021 ). This indicates that prefoldin is needed to respond to stress conditions and/or environmental changes.…”
Section: Non-canonical Functions Of the Prefoldin Complexmentioning
confidence: 99%
“…Interestingly, the study showed that degradation of HY5 occurred in COP1-independent manner ( Perea-Resa et al, 2017 ). Based on the findings, it is anticipated that prefoldin contributes indirectly through participation in cellular proteostasis to regulate the stability of TFs or complexes involved in different stages of gene expression ( Blanco-Touriñán et al, 2021 ). Figure 2 provides a schematic diagram on translational and post-translational modifications affecting CBF-dependent signaling for cold acclimation that has been discussed.…”
Section: Controlled Of Transcription Factor Levels Through Differenti...mentioning
confidence: 99%